Evaluating maternal drug use disparities, risk factors and outcomes in Northeast Arkansas: a pre, during, and post-COVID-19 pandemic analysis - Enrique Gomez Pomar; Johnna Berryhill; Sudeepa Bhattacharyya (BMC Public Health)
Abstract Introduction The use of addictive substances remains a major health problem in the U.S. An increase in drug overdose and mortality was observed during the COVID-19 pandemic, especially in underserved populations. This surge also impacted pregnant women especially with the use of marijuana (THC) and opioids. Methods Retrospective study analyzing mother-infant dyads with reported Meconium Drug Screen (MDS) results, from January 2018 through April 2023 at a reference hospital serving an urban and rural area of Arkansas. Due to the absence of universal screening, the prevalence of drug use was variable during the study period. An adjusted monthly positive rate (AMPR) was calculated by considering the expected number of positive MDS screenings per month and adjusting it based on the screening rate per month and the monthly birth count. Results Among 8,030 live births, 957 dyads were included in the analysis, with 47% (N = 450) of infants testing positive for at least one substance. Of these, 64.2%, 11.1%, and 6.7% were positive for THC, amphetamines, and opioids, respectively; and 17.8% tested positive for more than one substance. Infants with a positive MDS (MDS+) had significantly lower weight, height and head circumference with higher preterm rates and longer hospital stays. Mothers who smoked during pregnancy were more than twice as likely to have an MDS + result than those who did not (OR 2.39 (95% CI: 1.34–3.02), and most were from metropolitan areas (73%) or white (67%). The adjusted MDS + rate or AMPR significantly increased over the study period from 6.8% (January 2018) to 7.4% (April 2023). However, the COVID-19 pandemic did not significantly impact these rates. Compared to amphetamines and opioids, THC usage significantly increased during the study period and this increase was more pronounced after the state’s legalization of THC. Conclusion Maternal substance use, predominantly THC, continues to increase, particularly following its legalization. Infants who were MDS + presented adverse neonatal outcomes, with the majority of the mothers being white and from urban settings. Maternal self-reported smoking was associated with increased usage of other substances. Racial disparities were observed during the study, underscoring the need for universal drug testing and targeted interventions.